2023
DOI: 10.1001/jamadermatol.2023.3830
|View full text |Cite
|
Sign up to set email alerts
|

Janus Kinase Inhibitors and Adverse Events of Acne

Jeremy Martinez,
Cyriac Manjaly,
Priya Manjaly
et al.

Abstract: ImportanceJanus kinase (JAK) inhibitors are increasingly used across a range of dermatologic conditions. Adverse events of acne have been noted in some studies in clinical practice, but the scope of this outcome across JAK inhibitors has not been established.ObjectiveTo systematically analyze all published phase 2 and 3 placebo-controlled randomized clinical trials (RCTs) of JAK inhibitors for the risk of acne as an adverse effect of these medications.Data SourcesComprehensive search of Ovid MEDLINE and PubMed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 56 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…All events of acne, urticaria, and folliculitis were mild to moderate in severity. Acne has been reported as a common or very common adverse drug reaction for all JAK inhibitors approved for dermatological conditions [ 25 – 30 ]. While no clear mechanism of action is known for this, it has been suggested that JAK inhibitors may be associated with skin dysbiosis, including microbial colonization of Demodex folliculorum .…”
Section: Discussionmentioning
confidence: 99%
“…All events of acne, urticaria, and folliculitis were mild to moderate in severity. Acne has been reported as a common or very common adverse drug reaction for all JAK inhibitors approved for dermatological conditions [ 25 – 30 ]. While no clear mechanism of action is known for this, it has been suggested that JAK inhibitors may be associated with skin dysbiosis, including microbial colonization of Demodex folliculorum .…”
Section: Discussionmentioning
confidence: 99%